Proteomic profiling reveals mitochondrial dysfunction in the cerebellum of transgenic mice overexpressing DYRK1A, a Down syndrome candidate gene - Ortega, Mireia; De Toma, Ilario; Fernández-Blanco, Álvaro; Calderón, Anna; Barahona, Lucía; Trullàs, Ramón; Sabidó, Eduard; Dierssen, Mara (Frontiers in Molecular Neuroscience, 2022)
DYRK1A is a dual-specificity kinase that is overexpressed in Down syndrome (DS) and plays a key role in neurogenesis, neuronal differentiation and function, cognitive phenotypes, and aging. Dyrk1A has also been implicated in cerebellar abnormalities observed in association with DS, and normalization of Dyrk1A dosage rescues granular and Purkinje cell densities in a trisomic DS mouse model. However, the underlying molecular mechanisms governing these processes are unknown. To shed light on the effects of Dyrk1A overexpression in the cerebellum, here we investigated the cerebellar proteome in transgenic Dyrk1A overexpressing mice in basal conditions and after treatment with green tea extract containing epigallocatechin-3-gallate (EGCG), a DYRK1A inhibitor. Our results showed that Dyrk1A overexpression alters oxidative phosphorylation and mitochondrial function in the cerebellum of transgenic mice. These alterations are significantly rescued upon EGCG-containing green tea extract treatment, suggesting that its effects in DS could depend in part on targeting mitochondria, as shown by the partially restoration by the treatment of the increased mtDNA copy number in TG non-treated mice.